Comparison of used ground coffee and sawdust mixture as substrates of oyster mushroom (Pleurotus Ostreatus) - Afiqah Wadi'ah Abdul Muin (2016)
Comparison of used ground coffee and sawdust mixture as substrates of oyster mushroom (Pleurotus Ostreatus) "A field experiment was conducted at the Faculty of Sustainable Agriculture in Universiti Malaysia Sabah, Sandakan, Sabah to investigate the comparison of used ground coffee (UGC) and sawdust mixture (SM) as substrates of oyster mushroom (Pleurotus ostreatus). The oyster mushroom, P. ostreatus was cultivated on used ground coffee and sawdust mixture with different percentage ratio in polyethene bags. The five treatments used are Treatment 1 (100% SM), Treatment 2 (75% SM, 25% UGC), Treatment 3 (50% SM, 50% UGC), Treatment 4 (25% SM, 75% UGC) and Treatment 5 (100% UGC). Each treatment was replicated five times. Completely Randomized Design (CRD) was used in this experiment. The spawning was done after the sterilization of the substrate bag then being left for incubation for 33 days with the temperature of 20-25°C and 75-90% relative humidity. Mycelium run rate, time taken for pinhead formation stage, biological efficiency, fresh weight of mushroom and total yield were measured and all data was analyzed using one way Variance Analysis Test (ANOVA) and Tukey analysiS is used to analyze the difference of the average mean for each treatment at 5% level of significance. The experiment result indicates that there are significant difference of mycelium run rate, time taken for pinhead formation stage, biological efficiency, mushroom fresh weight and total yield. For Treatment 1 and Treatment 5 the mean for mycelium run rate, time taken for pinhead formation stage, biological efficiency, fresh weight of mushroom and total yield are 0.00 respectively. While for Treatment 2, Treatment 3 and Treatment 4, mean for mycelium run rate was 0.378 cm/day, 0.394 cm/day and 0.314 cm/day; mean for time taken for pinhead formation stage was 6.8 days, 9.8 days and 12.0 days; mean for biological efficiency was 0.354 %, 13.680 % and 5.984 %; mean for fresh weight of mushroom was 0.610 g, 25.262 g and 11.374 g and mean for total yield was 0.00354 gig, 0.13678 gig and 0.05984 gig respectively. The result obtained from the experiment in this study indicates that there is potential of using used ground coffee (UGC) as an alternative substrate of oyster mushroom other than using sawdust mixture (SM) substrate.